Protonation of carbene-stabilized diphosphorus: complexation of HP2+. Issue 33 (5th April 2016) - Wang, Yuzhong; Hickox, Hunter P.; Xie, Yaoming; Wei, Pingrong; Cui, Dongtao; Walter, Melody R.; Schaefer III, Henry F.; Robinson, Gregory H.
Abstract : The highly reactive HP2 + cation has been stabilized by carbene coordination. Abstract : Reaction of carbene-stabilized diphosphorus, L:P–P:L (5 ) (L: = :C{N(2, 6-Pr i 2 C6 H3 )CH}2 ) with pyridine hydrochloride yields [L:(H)P–P:L]Cl (6 ), a salt containing the HP2 + cation—the elusive phosphorus analogue of the well known diazonium cation, HN2 + . In addition to reporting the synthesis and structure, the nature of (6 ) was further probed by DFT computations. Interestingly, carbenes may be employed to deprotonate (6 ), affording the starting material (5 ).